Biocontrol potential of native entomopathogenic nematodes in controlling red hairy caterpillar (Amsacta albistriga) (Lepidoptera :Arctiidae) of groundnut (Arachis hypogaea) - BASKARAN, R K MURALI; SIVAKUMAR, C V; VENUOOPAL, M S (The Indian Journal of Agricultural Sciences, 2013)
The efficacy of an entomopathogenic nematode,Â SteinernemaÂ carposapsae Weiser (strain DD 136), and 3 native isolates. designated Heterorhabditis bacteriophora Poinar (strain Burliar). Heterorhabditis sp (strain Chekkanurani) and Heterorhaditis sp (strain Melur). was tested during 1992 for controlling fourth-instar larvae of red hairy caterpillar [Amsacta albistriga (Walker)] of ground nut (Arachis hypogaea L.). The nematode was used at 5 concentrations (0,5, 10,20 and 40 infective juveniles/larva) and estimated Lethal concentration 50 (LT50). The efficacy of the nematode depended on its population level. Among the 4 nematodes. S. carpocapsae was the most effective in killing the larvae, followed by Heterorhabditis sp (strain Chekkanurani). having LC50 respectively 6.5 and 8.3Â nematodes/larva at 84 hr after inoculation. Similarly. LT50@ 20 infective juveniles/larva was 3.1-5.5 days. Absence of dauers in the dead larvae indicated that the host tissue prevented the development of 3 native Heterorhabditis sp. But the host insect died because of symbiotic bacterial population, whereas S. carpocapsae killed the host by completing its life-cycle.